Towards global carbon pricing Direct and indirect linking of carbon markets - Dellink, Rob (OECD Publishing, 2014)
Emissions trading systems (ETS) can play a major role in a cost-effective climate policy framework. Both direct linking of ETSs and indirect linking through a common crediting mechanism can reduce costs of action.We use a global recursive-dynamic computable general equilibrium model to assess the effects of direct and indirect linking of ETS systems across world regions. Linking of domestic Annex I ETSs leads to moderate aggregate cost savings, as differences in domestic permit prices are limited. Countries benefit directly from linking by either buying permits and avoiding investing in highcost mitigation options, or by exploiting relatively cheap mitigation options and selling permits at a higher price. Although the economy of the main permit sellers, such as Russia, is negatively affected by the real exchange rate appreciation that is induced by the large export of permits, on balance they also still benefit from linking. The costsaving potential for developed countries of well-functioning crediting mechanisms appears to be very large. Even limited use of credits would nearly halve mitigation costs; cost savings would be largest for carbon-intensive economies. However, one open issue iswhether these gains can be fully reaped in reality, given that direct linking and the use of crediting mechanisms both raise complex system design and implementation issues. The analysis in this paper shows, however, that the potential gains to be reaped are so large, that substantial efforts in this domain are warranted. JEL classification: H23, O41, Q54 Keywords: Climate mitigation policy, emissions trading systems, general equilibrium models, linking carbon markets